Business Process Management / Διάλεξη 3 / Performance Management - Three Different Levels of Concern - Πολυχρονάκη Χριστίνα (ΟΙΚΟΝΟΜΙΚΟ ΠΑΝΕΠΙΣΤΗΜΙΟ ΑΘΗΝΩΝ, 2016)
Performance Management - Three Different Levels of Concern